2012
DOI: 10.1029/2011je003981
|View full text |Cite
|
Sign up to set email alerts
|

The origin of Ina: Evidence for inflated lava flows on the Moon

Abstract: Ina is an enigmatic volcanic feature on the Moon known for its irregularly shaped mounds, the origin of which has been debated since the Apollo Missions. Three main units are observed on the floor of the depression (2.9 km across, ≤64 m deep) located at the summit of a low‐shield volcano: irregularly shaped mounds up to 20 m tall, a lower unit 1 to 5 m in relief that surrounds the mounds, and blocky material. Analyses of Lunar Reconnaissance Orbiter Camera images and topography show that features in Ina are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(100 citation statements)
references
References 60 publications
2
98
0
Order By: Relevance
“…We thus favor the deep basal/subcrustal origin for the magma reservoirs for both cases ( Figure 15) and do not require the shallow near-surface magma reservoir proposed by Jolliff et al (2011Jolliff et al ( , 2012 for the CBVC (Figure 32c), instead finding that the low density of the magma, assisted by a potentially high volatile (OH) content (Bhattacharya et al, 2013;Petro et al, 2013), could readily assist magma ascent, and favor effusive and explosive eruptions (Wilson et al, 2014;Wilson and Head, 2016a,b). El Baz, 1973;Strain and El Baz, 1980;Garry et al, 2012) interpreted by many to represent very young mare volcanic activity (Figure 1c) (Schultz et al, 2006, suggested ~10 Ma). Using LRO Narrow Angle Camera images, digital terrain models and Wide…”
Section: G Non-mare Volcanic Domes and Complexes: Relation To Basaltmentioning
confidence: 93%
See 1 more Smart Citation
“…We thus favor the deep basal/subcrustal origin for the magma reservoirs for both cases ( Figure 15) and do not require the shallow near-surface magma reservoir proposed by Jolliff et al (2011Jolliff et al ( , 2012 for the CBVC (Figure 32c), instead finding that the low density of the magma, assisted by a potentially high volatile (OH) content (Bhattacharya et al, 2013;Petro et al, 2013), could readily assist magma ascent, and favor effusive and explosive eruptions (Wilson et al, 2014;Wilson and Head, 2016a,b). El Baz, 1973;Strain and El Baz, 1980;Garry et al, 2012) interpreted by many to represent very young mare volcanic activity (Figure 1c) (Schultz et al, 2006, suggested ~10 Ma). Using LRO Narrow Angle Camera images, digital terrain models and Wide…”
Section: G Non-mare Volcanic Domes and Complexes: Relation To Basaltmentioning
confidence: 93%
“…Mass balance calculations (Wilson et al, 2013) find that the predicted void spaces at the top of dikes can readily account for the missing volumes of regolith material by drainage. Similar processes may operate on more ancient lava flows that were emplaced in an inflationary mode, leaving near-subsurface void spaces which later form IMP-like features due to collapse and drainage of regolith (Garry et al, 2012;Qiao et al, 2016b). Others, such as the Ina feature, which occurs as the summit pit crater on a small lava shield (Figure 32a), are consistent with a two component origin as a drained lava lake (forming the mounds as kipukas, and the floor as a void-rich subsided lava lake crust) followed by differential development of regolith (normal development on the mounds, and abnormal development on the floor as seismic sieving causes small regolith particles to preferentially drain into the underlying voids, maintaining roughness and optical immaturity, and exposing boulders) (Qiao et al, 2016c).…”
Section: H Irregularmentioning
confidence: 96%
“…Schultz et al () examined the topographic relief, superposed impact crater populations and optical maturity of Ina, and suggested that Ina floor units originated from the removal of fine‐grained surface materials by episodic outgassing within the past 10 Ma, and that they are perhaps still active today. Garry et al () called on terrestrial analogs (specifically, the McCarty's inflated lava flow field in New Mexico) and found that the Ina interior terrains have comparable dimensions and topographic relief to some terrestrial inflated lava flows and interpreted Ina as being formed through inflated lava flows (the mounds) followed by lava breakouts from the mound margins that built the hummocky units.…”
Section: Introductionmentioning
confidence: 99%
“…These surface physical properties suggest either that Ina is older than its calculated crater retention ages or that Ina is indeed <100 Ma old, but its surface accumulates regolith more rapidly than blocky ejecta deposits. Elder et al () proposed that some form of explosive activity, either pyroclast deposition (Carter et al, ) or another style of outgassing (Schultz et al, ) was likely to have been involved in the formation of Ina, though the possibility of lava flow inflation (Garry et al, ) or regolith drainage into subsurface void space (Qiao et al, ) could not be precluded; however, the specific formation mechanism and emplacement sequences of the various morphologic units within Ina were not detailed by Elder et al ().…”
Section: Introductionmentioning
confidence: 99%
“…No cracks or inflation clefts are observed in the study area, as required on Earth for a flow's brittle crust to accommodate endogenous growth via inflation (Walker, 1991;Hon et al, 1994; a similar problem when suggesting that the Ina D feature on the Moon is associated with lava flow inflation. At that site a series of smoothtopped plateaus within a larger depression are suggested by Garry et al (2012) to have formed via lava inflation, but no clefts are present. The Tharsis region of Mars is well known to be covered by a pervasive dust deposit (Ruff and Christensen, 2002) thick enough to obscure orbital spectral observations, and in high resolution image data dust mantles are often seen to mute or completely bury surface textural information beneath dunes.…”
Section: Discussionmentioning
confidence: 99%